2013
DOI: 10.1080/01292986.2013.839725
|View full text |Cite
|
Sign up to set email alerts
|

‘No hugging please, we are Muslims’:Akademi Fantasia, Malay television audiences and the negotiation of global popular cultural forms

Abstract: This paper analyses the audience reception of the Malaysian reality television programme Akademi Fantasia (AF), which first aired in 2003 and completed its ninth season in 2011. AF has been an influential pioneer in the national television industry, inaugurating the trend of local reality shows and weathering intense competition from similar shows to remain at the top of the ratings chart over the last decade. Based on the Mexican talent search show, La Academia, Malaysia's AF is a unique hybrid blend of an Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A number of studies have shown that Malaysian consumers adopt a different lens when it comes to the popular culture (e.g. Shamshudeen & Morris, 2014;Moschis & Ong, 2011;Shah Alam et al,2011). Despite their interest in celebrity, most Malaysian still try to stay true to their faith, belief and cultural norms.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that Malaysian consumers adopt a different lens when it comes to the popular culture (e.g. Shamshudeen & Morris, 2014;Moschis & Ong, 2011;Shah Alam et al,2011). Despite their interest in celebrity, most Malaysian still try to stay true to their faith, belief and cultural norms.…”
Section: Introductionmentioning
confidence: 99%
“…Because of such recurrence and dominance, we press these issues further, describing youth's experience with the TV fiction that permit them to make connections with their Malay 'local. ' Secondly, although previous recent readings by Chong (2005), Dahlia (2010Dahlia ( , 2012, Hussin (1993), liow (2009), Martinez (2004, Maznah (2008), norman (2011), Peletz (2005, Rosya (2011), Rosya and Morris (2014), Ruzy and Shahizah (2010), Syed (2011aSyed ( , 2011bSyed ( , 2011c, Syed and Hamzah (2012), Runnel (2013), andWeiss (2004) have examined broadly on Malay traditions, aspects of forgiveness and repentance receive lack of attention. By examining these issues, we realign TV fiction and rediscovery of Malay 'local' by exploring youth's voices as the ensuing discussion will demonstrate.…”
Section: Introductionmentioning
confidence: 99%
“…The critical unpacking of the sociocultural undercurrents of contemporary beauty pageant contests involves the construction of ‘idealized femininity’, which includes an emphasis on distinct sets of skills, divergent ways of managing appearances and dress and varied class strategies to fit the politico-cultural desired modes of modern femininity (Balogun, 2012: 364). Studies across the world have alluded to the structuring of the beauty pageants across diverse socio-economic and cultural contours of femininity that encompasses both traditionalized femininity and contemporary mobility (Parameswaran, 2006) and the multifaceted means by women in negotiating these changing circumstances (Jones, 2010; Kariksei and McLamey, 2010; Mousier, 2007; Shamshudeen and Morris, 2013; Syed, 2013). Through the case studies of the two televised beauty contests, this article intends to position the concepts of ethnocultural mobility and positional femininity as part of the televisual idealization of beauty in Singapore.…”
Section: Introduction: Idealized and Positional Femininitymentioning
confidence: 99%